2022
DOI: 10.1161/circep.121.009925
|View full text |Cite
|
Sign up to set email alerts
|

Sex-Related Differences in Atrial Remodeling in Patients With Atrial Fibrillation: Relationship to Ablation Outcomes

Abstract: Background: Population studies have demonstrated a range of sex differences including a higher prevalence of atrial fibrillation (AF) in men and a higher risk of AF recurrence in women. However, the underlying reasons for this higher recurrence are unknown. This study evaluated whether sex-based electrophysiological substrate differences exist to account for worse AF ablation outcomes in women. Methods: High-density electroanatomic mapping of the left a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
1
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(49 citation statements)
references
References 28 publications
1
37
1
4
Order By: Relevance
“…Some reports found sex differences in the AF recurrence ( 7 , 8 , 39 ). Consistent with the above results, this study demonstrated that women experienced a higher incidence of post-ablation AF recurrence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some reports found sex differences in the AF recurrence ( 7 , 8 , 39 ). Consistent with the above results, this study demonstrated that women experienced a higher incidence of post-ablation AF recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…Matrix metalloproteinases, a vital modulator of extracellular matrix turnover that contributes to atrial fibrosis, were upregulated in the AF period, and their secretion increased within EAT ( 37 , 38 ). An existing study reported that female patients with AF had more advanced atrial remodeling compared with male patients ( 39 ).…”
Section: Discussionmentioning
confidence: 99%
“…Multiple risk factors, including unmodifiable risk factors (e.g., gender, age, and genetics) and modifiable risk factors (e.g., hypertension, DM, and obesity), played a significant role in contributing to the initiation and progression of AF. A growing number of clinical studies have suggested that female patients have a higher risk of AF recurrence than male patients after ablation, owing to more advanced atrial remodeling [ 44 , 45 ]. The recurrent AF subanalysis in the CABANA trial (NCT00911508) proved that the efficacy of ablation in the female subgroup was significantly inferior to that in the male subgroup when compared with the efficacy of drug therapy (HR: 0.64 vs. 0.46, p for interaction = 0.035) [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“… 37 More advanced atrial remodeling and a greater number of recurrences have been shown after AF ablation in females despite AF duration similar to males. 38 In contrast, a systematic review reported that none of the more than 20 included studies found female sex to be a predictor of AF recurrence after AF ablation. 39 Furthermore, the AXAFA-AFNET 5 study showed similar improvement in quality of life in both sexes after ablation.…”
Section: Sex Disparitiesmentioning
confidence: 98%